2013
DOI: 10.1080/10826068.2012.693899
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON OF ARTIFICIAL NEURAL NETWORK (ANN) AND RESPONSE SURFACE METHODOLOGY (RSM) IN OPTIMIZATION OF THE IMMOBILIZATION CONDITIONS FOR LIPASE FROMCandida rugosaON AMBERJET® 4200-Cl

Abstract: Candida rugosa lipase (CRL) is an important industrial enzyme that is successfully utilized in a variety of hydrolysis and esterification reactions. This work describes the optimization of immobilization conditions (enzyme/support ratio, immobilization temperature, and buffer concentration) of CRL on the anionic resin Amberjet® 4200-Cl, using enantioselectivity (E) as the reference parameter. The model reaction used for this purpose is the acylation of (R,S)-1-phenylethanol. Optimal conditions for immobilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…There was no shift observed at the optimum pH for the CLEA lipase formed (pH 8.0), in comparison with that of free lipase despite any conformational changes possibly occurring during immobilization (Mateo et al, ). It has been reported that the free Cal B lipase exhibits maximum activity under basic conditions (pH 7.0–8.0) due to the stability maintained by the structure and maintenance of the open, active structural configuration under these conditions (Fatiha et al, ). No difference in the activity between free and CLEA lipase was observed at pH 8.0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no shift observed at the optimum pH for the CLEA lipase formed (pH 8.0), in comparison with that of free lipase despite any conformational changes possibly occurring during immobilization (Mateo et al, ). It has been reported that the free Cal B lipase exhibits maximum activity under basic conditions (pH 7.0–8.0) due to the stability maintained by the structure and maintenance of the open, active structural configuration under these conditions (Fatiha et al, ). No difference in the activity between free and CLEA lipase was observed at pH 8.0.…”
Section: Resultsmentioning
confidence: 99%
“…CLEA lipase exhibited a lower stability compared to free enzyme at pH 6.0, with 80% of the initial activity maintained after prolonged exposure of up to 240 min. This may be attributed to the conformational changes that could be occurring during the CLEA formation process, making the CLEA unstable under slightly acidic conditions of pH 6.0, despite maintaining high activity under basic conditions (Fatiha et al, ; Gupta et al, ) (Fig. b).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the MLR and ANN model shows that the effect of some of the descriptors to activity may be non-linear [6]. Fatiha et al (2013) have been investigated optimal conditions for immobilization, through RSM and ANN. They have concluded that both models provided good quality predictions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Fatiha et al (2013) have been investigated optimal conditions for immobilization, through RSM and ANN. They have concluded that both models provided good quality predictions [7]. Vasundara et al (2014) carried out research to predict the maximum elastic deformation of the workpiece during machining for the fixture layout.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method is limited in most cases by the use of polynomial equations. Instead, ANNs can be used to ensure better data fit and estimation capabilities (Ba & Boyaci, 2007; Fatiha et al 2013).…”
mentioning
confidence: 99%